Screening and characterization of amylase enzyme in sweet orange (Citrus sinensis) juice clarification - ROHULA UTAMI; ESTI WIDOWATI; ACCESSTIA CHRISTY (Smujo International, 2016)
Abstract. Utami R, Widowati E, Christy A. 2016. Screening and characterization of amylase enzyme in sweet orange (Citrus sinensis) juice clarification. Nusantara Bioscience 8: 268-272. The amylum compound of sweet orange cloudify the produced juice. Clarification by amylase could remove the cloudiness. The aimed of this study were screening the amylolytic bacteria from spoiled potato which are potential in clarification of sweet orange juice, and characterization of the resulted amylase (optimum pH and temperature, pH and thermal stability, KM and Vmax). The results showed that from thirteen bacterial isolates, three isolates (K-7, K-8, and K-11) produced enzymes that showed the best clarification activity on the sweet orange juice. The optimum pH of the isolate K-7, K-8, and K-11 enzymes were found to be 7, 7 and 6, respectively. The optimum temperature of the isolate K-7, K-8, and K-11 enzymes were found to be 35, 40 and 35°C, respectively. Enzymes of isolate K-7, K-8, and K-11 were stable in the pH range 3-6, 5-6, and 7-8, respectively. The enzyme of isolate K-7 and K-11 were stable at temperature 40-60°C while enzyme of isolate K-8 stable at temperature 40-70° C. Km values of isolate K-7, K-8, and K-11 enzymes were 0.2756 mg/mL, 0.0888 mg/mL, and 0.0956 mg/mL, respectively. Vmax values of isolate K-7, K-8, and K-11 enzyme were 0.0325 U/mL, 0.0164 U/mL, and 0.0134 U/mL.